Contribution of a lectin, LecM, to the quorum sensing signalling pathway of Ralstonia solanacearum strain OE1‐1. (6th November 2018) - Hayashi, Kazusa; Kai, Kenji; Mori, Yuka; Ishikawa, Shiho; Ujita, Yumeto; Ohnishi, Kouhei; Kiba, Akinori; Hikichi, Yasufumi
Summary: The soil‐borne bacterium Ralstonia solanacearum invades the roots and colonizes the intercellular spaces and then the xylem. The expression of lecM, encoding a lectin LecM, is induced by an OmpR family response regulator HrpG in R. solanacearum strain OE1‐1. LecM contributes to the attachment of strain OE1‐1 to the host cells of intercellular spaces. OE1‐1 produces methyl 3‐hydroxymyristate (3‐OH MAME) through a methyltransferase (PhcB) and extracellularly secretes the chemical as a quorum sensing (QS) signal, which activates QS. The expression of lecM is also induced by the PhcA virulence regulator functioning through QS, and the resulting LecM is implicated in the QS‐dependent production of major exopolysaccharide EPS I and the aggregation of OE1‐1 cells. To investigate the function of LecM in QS, we analysed the transcriptome of R. solanacearum strains generated by RNA sequencing technology. In the lecM mutant, the expression of positively QS‐regulated genes and negatively QS‐regulated genes was down‐regulated (by >90%) and up‐regulated (by 60%), respectively. However, phcB and phcA in the lecM mutant were expressed at levels similar to those in strain OE1‐1. The lecM mutant produced significantly less ralfuranone and exhibited a significantly greater swimming motility, which were positively and negatively regulated by QS, respectively. In addition, the extracellular 3‐OH MAME content of the lecM mutant was significantly lower than that of OE1‐1. The application of 3‐OH MAME more strongly increased EPS I production in the phcB ‐deleted mutant and strain OE1‐1 than in the lecM mutant. Thus, the QS‐dependent production of LecM contributes to the QS signalling pathway.